PENGARUH PRESTASI BELAJAR MATA PELAJARAN AKHLAK TERHADAP TINGKAH LAKU PROSOSIAL SISWA KELAS IX DI SMP MUHAMMADIYAH CILONGOK TAHUN AJARAN 2017/2018 - Muhandis, Rizki Nazia (AS-SALAM, 2018)
This scientific journal entitled "The Influence Of Learning Achievement Of Subject Of Morals To The Behavior Of Prosocial Students Of Class IX In SMP Muhammadiyah Cilongok Academic Year 2017/2018". The purpose of this study is to determine whether there is influence of learning achievement subjects morals to the behavior of students in the class IX prosedur SMP Muhammadiyah Cilongok academic year 2017/2018. Samples were taken using purposive sampling technique. Namely by taking students in class IX D and class IX G which amounted to 50 respondents. This research is a quantitative research with data collection tool in the form of questionnaire (questionnaire) scale and documentation. After the data collected then done the analysis by using the formula Product moment. The result shows that rxy is 0,344 and r table with significance level 5% (N = 50) equal to 0,273. It shows rxy> r table at 5% significance. While at 1% significance is rxy